Kalantaevska G. P. Еmotive-dramatical image system of J. Mamontov’s poetry - Kalantaevska G. P. (Philological Treatises, 2020)
This article deals with motives, moods, symbol-image system of the poems of J. Mamontov’s collection “Wreaths on the water”. It describes different features of a psychology-emotional portrait of the lyrical hero presented by the author as a spiritually rich person, who can reach introspection and meditation.